Perioral pigmentation - Siddharth Bhatt; Shekhar Neema; Biju Vasudevan (Wolters Kluwer Medknow Publications, 2022)
ABSTRACT Perioral pigmentation is a commonly encountered condition in the skin Out Patient Department (OPD), occurring due to a variety of primary as well as secondary causes. The affection of the perioral skin being readily visible negatively impacts the patient's quality of life. As the etiology of perioral pigmentation is multifactorial, treatment modalities vary according to the cause. The perioral skin, because of its location close to the mouth, is exposed to various allergens associated with food, saliva, toothpaste, cosmetics, etc., which can all lead to allergic manifestations resolving with pigmentation. Certain other dermatoses like melasma can first present with pigmentation over the perioral region. Infections like chikungunya and dengue and infestation with Demodex mite can also lead to pigmentation at this site. Perioral pigmentation can also be a marker of underlying systemic disease. Localized lentigines-like pigmentation can be associated with various cancer predisposition syndromes like Peutz-Jeghers syndrome. Diffuse pigmentation can occur due to Addison disease, vitamin deficiencies, or can be drug-induced. All these causes of pigmentation are seen more commonly in type IV and V skin. Currently, very little literature is available elucidating the cause of perioral pigmentation and the diagnostic approach. This article reviews the causes of perioral pigmentation and highlights their important features.